ASSESSING CONSUMER PERCEPTION AND PREFERENCE FOR FRESH OR PROCESSED CITRUS FRUITS: IMPLICATIONS FOR THE SWEET ORANGE SUPPLY CHAIN IN OYO STATE NIGERIA - Sanmi AJISOLA; Oluwafunmiso Adeola OLAJIDE; Foluso Temitope AGULANNA (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
This study investigated the level of substitution of fresh fruit for processed fruit and what influences consumers’ preference for purchase of fresh citrus or processed citrus in Oyo State. Well-structured questionnaires were used to collect information from 100 respondents using a two-stage sampling technique. Descriptive statistics and probit regression were used to analyze the relationship of socioeconomic factors and respondents’ opinion with regards their preference for fresh or processed citrus fruits. From the result of the study, a good number of respondents prefer fresh to processed citrus fruits. The study also revealed that the opinion or perception of the respondents in relation to cost of purchase, nutritional content, negative or positive implication on health influences their preference for fresh citrus while convenience, cost of purchase and nutritional content influence preference for processed citrus fruits. Majority of the respondents indicated that processed citrus may have negative health implications.